When affordances climb into your mind: Advantages of motor simulation in a memory task performed by novice and expert rock climbers - Pezzulo, Giovanni; Barca, Laura; Bocconi, Alessandro Lamberti; Borghi, Anna M. (Brain and cognition, 2010)
Does the sight of multiple climbing holds laid along a path activate a motor simulation of climbing that path? One way of testing whether multiple affordances and their displacement influence the formation of a motor simulation is to study acquired motor skills. We used a behavioral task in which expert and novice rock climbers were shown three routes: an easy route, a route impossible to climb but perceptually salient, and a difficult route. After a distraction task, they were then given a recall test in which they had to write down the sequence of holds composing each route. We found no difference between experts and novices on the easy and impossible routes, whereas on the difficult route, the performance of experts was better than that of novices. This suggests that seeing a climbing wall activates a motor, embodied simulation, which relies not on perceptual salience, but on motor competence. More importantly, our results show that the capability to form this simulation is modulated by individuals’ motor repertoire and expertise, and that this strongly impacts recall.